Age-dependent acute interference with stem and progenitor cell proliferation in the hippocampus after exposure to 1800 MHz electromagnetic radiation. (3rd April 2017) - Xu, Falin; Bai, Qiongdan; Zhou, Kai; Ma, Li; Duan, Jiajia; Zhuang, Fangli; Xie, Cuicui; Li, Wenli; Zou, Peng; Zhu, Changlian
ABSTRACT: To investigate the effects of exposure to an 1800 MHz electromagnetic field on cell death and cell proliferation in the developing brain, postnatal day 7 (P7) and P21 healthy Kunming mice were randomly assigned into the experimental and control groups. The experimental groups were exposed to an 1800 MHz electromagnetic field for 8 h daily for three consecutive days. The thymidine analog 5-bromo-2-deoxyuridine (BrdU) was injected intraperitoneally 1 h before each exposure session, and all animals were sacrificed 24 h after the last exposure. Cell death and proliferation markers were detected by immunohistochemistry in the dentate gyrus of the hippocampus. Electromagnetic exposure has no influence on cell death in the dentate gyrus of the hippocampus in P7 and P21 mice as indicated by active caspase-3 immunostaining and Fluoro-Jade labeling. The basal cell proliferation in the hippocampus was higher in P7 than in P21 mice as indicated by the number of cells labeled with BrdU and by immunohistochemical staining for phosphor-histone H3 (PHH3) and brain lipid-binding protein (BLBP). Electromagnetic exposure stimulated DNA synthesis in P7 neural stem and progenitor cells, but reduced cell division and the total number of stem cells in the hippocampus as indicated by increased BrdU labeling and reduced PHH3 and BLBP labeling compared to P7 control mice. There were no significant changes in cell proliferation in P21 mice after exposure to the electromagnetic field. These results indicate that interference with stem cell proliferation upon short-term exposure to an 1800 MHz electromagnetic field depends on the developmental stage of the brain.